Feminism and conservative Christian women: the history making possible the dialogue - Meira, Vanessa (Vox Scripturae - Revista Teológica Internacional, 2017)
This article will reflect on the influence of Christianity on women’s emancipation movements that composed the First Wave of Feminism of the nineteenth and twentieth centuries. A pattern of opportunities for women’s participation and leadership is founded in many egalitarian Christian movements. However, egalitarian Christian movements are often overlooked in academic research and popular publications on the origins of the movement of women’s rights. Such negligence is unjustifiable. In this article, through historical literature review, will be highlighted the Christian heritage of feminism in the United States. The article reveals that shed light on the religious roots of feminism can inspire religious women who don’t have sympathy for contemporary feminism because of anticlericalism and strong criticism against Christianity by sectors of the movement.
Keywords: Feminism; Quakerism; Conservatism; Suffragism